THEORIES OF POSTMODERNITY: SOCIAL PROJECT? SOCIAL FORECASTING? UTOPIA? - Drotianko, Liubov (Proceedings of the National Aviation University Series Philosophy Cultural, 2023)
Introduction. An urgent task of philosophy and other social sciences is to analyze to what extent the characteristics of the society that replaced the Modern one, being represented in the postmodern theories, correspond to the realities of the ХХI century; how scientific the mentioned social projects and forecasts turned out to be. The aim of the research is to comprehend the theories of Postmodernity as those that outlined the characteristic features of the future society which beginning could be found in the bowels of Modernity at the end of the XX century. The postmodern theories are being compared in order to identify the possibility of referring them to social projects, social forecasting, or social utopias. Research methods. The research uses the cultural-historical and sociocultural approaches, the comparative method, methods of logical and cultural-semantic analysis, hermeneutical procedures of interpretation and understanding. Research results. The philosophical theories of Postmodernity of J.-F. Lyotard, P. Kozlowski, and W. Welch are analyzed in order to determine the actualization of the ideas they set forth in the ХХ century. It is shown that the change in the role and status of scientific knowledge and higher education is most represented in the concept of J.-F. Lyotard. The pragmatic nature of transformations in the development of scientific knowledge in the Postmodern era is revealed. The concept of P. Kozlowski is largely concerned with the harmonization of relations between scientific and religious knowledge. Discussion. The research presents the views of F. Webster and a number of national philosophers on the main features of the Postmodern era, which relate to the development of science and its legitimization in higher education in the XXI century. Conclusions. It is substantiated that J.-F. Lyotard's concept of Postmodernity is the most developed in terms of understanding the changes in science and higher education. It is concluded that this concept can be attributed to social forecasting. The ideas expressed by P. Kozlowski are considered to be rather utopian.